2023
DOI: 10.1101/2023.08.02.551736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Dependence and Genetic Diseases

Bin Li,
Wen-Jun Bian,
Peng Zhou
et al.

Abstract: The human life depends on the function of proteins that are encoded by about twenty-thousand genes. The gene-disease associations in majority genes are unknown and the mechanisms underlying pathogenicity of genes/variants and common diseases remain unclear. We studied how human life depends on the genes, i.e., the genetic-dependence, which was classified as genetic-dependent nature (GDN, vital consequence of abolishing a gene), genetic-dependent quantity (GDQ, quantitative genetic function required for normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Our previous study showed that genes differ in expression stage and is potentially correlated with the onset age. 8,28 CCDC88C is expressed in the fetal brain, with an intermission after birth, and increases aging in the adult brain, consistent with the onset age of the patients in this study. In addition, gene expression stage is also potentially associated with evolution of genetic diseases.…”
Section: Clinical Features Of the Cases With Ccdc88c Variantssupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous study showed that genes differ in expression stage and is potentially correlated with the onset age. 8,28 CCDC88C is expressed in the fetal brain, with an intermission after birth, and increases aging in the adult brain, consistent with the onset age of the patients in this study. In addition, gene expression stage is also potentially associated with evolution of genetic diseases.…”
Section: Clinical Features Of the Cases With Ccdc88c Variantssupporting
confidence: 88%
“…The differences of onset age of seizures are also potentially associated with gene expression stage. Our previous study showed that genes differ in expression stage and is potentially correlated with the onset age 8,28 . CCDC88C is expressed in the fetal brain, with an intermission after birth, and increases aging in the adult brain, consistent with the onset age of the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that GDS is associated with the natural course and outcomes of diseases. 14,[34][35][36] In this study, the two patients with early spasms presented favorable outcomes. Studies on the temporal expression stage showed that ZFHX3 orthologs were highly expressed in the embryonic stage and decreased dramatically in childhood, which is potentially one of the explanations for the favorable outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Among the novel candidate genes, SBF1 presents dominant inheritance (heterozygous de novo variants in three cases), and the remaining majority of candidate genes present recessive inheritance, including XLR. This could be basically understood by the quantitative dependent feature of genes 47,48 . We defined the lowest limit of the required quantity of genetic function of the gene as the genetic dependent quantity (GDQ).…”
Section: Discussionmentioning
confidence: 99%
“…We defined the lowest limit of the required quantity of genetic function of the gene as the genetic dependent quantity (GDQ). If the full scale of GDQ was set at 100% with contributions from two copies of a gene, the genes with GDQ < 50% are much more abundant (https://gdap.org.cn/) 47,48 , since the human genome is diploid and usually a portion of functioning from one copy of a gene is sufficient for biophysiological function. Subsequently, pathogenic recessive (including X-linked recessive) variants are potentially common.…”
Section: Discussionmentioning
confidence: 99%